2012
DOI: 10.1590/s1413-81232012000400009
|View full text |Cite
|
Sign up to set email alerts
|

Despesa pública municipal com saúde em Pernambuco, Brasil, de 2000 a 2007

Abstract: Com o objetivo de identificar o impacto produzido pelas medidas de macropolítica postas em prática na segunda metade dos anos noventa no crescimento do valor da despesa pública com saúde e na possível redução da desigualdade alocativa, foi realizado um estudo descritivo, transversal, de natureza quantitativa, abrangendo os 184 municípios de Pernambuco. Utilizaram-se dados do Sistema de Informações sobre Orçamentos Públicos em Saúde, elegendo-se como indicador a Despesa com saúde sob a responsabilidade do munic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
1
3
0
3
Order By: Relevance
“…This fact may be explained by increased municipal public expenditure in that region, as indicated by a study on public health expenditure in the state of Pernambuco in the period from 2000 to 2007. 29 The good performance of oral health care in this health region has been confirmed by other studies, which found a considerable decrease in the number of tooth extraction procedures in municipal public health services between 2000 and 2008, 30 and the improvement of the "first programmatic consultation coverage" indicator in these municipalities, when comparing 2001 data with 2009 data. 5 In relation to the high averages of dental urgency identified in this region, even though almost all its municipalities had 100% OHt population coverage, this situation may be related to high unmet demand and low appraisal of completed treatment.…”
Section: Quality Of Oral Health Caresupporting
confidence: 56%
“…This fact may be explained by increased municipal public expenditure in that region, as indicated by a study on public health expenditure in the state of Pernambuco in the period from 2000 to 2007. 29 The good performance of oral health care in this health region has been confirmed by other studies, which found a considerable decrease in the number of tooth extraction procedures in municipal public health services between 2000 and 2008, 30 and the improvement of the "first programmatic consultation coverage" indicator in these municipalities, when comparing 2001 data with 2009 data. 5 In relation to the high averages of dental urgency identified in this region, even though almost all its municipalities had 100% OHt population coverage, this situation may be related to high unmet demand and low appraisal of completed treatment.…”
Section: Quality Of Oral Health Caresupporting
confidence: 56%
“…Meanwhile, GDP per capita had a negligible effect on the incidence of the disease. Furthermore, the values were distributed quite unevenly among the regions, which demonstrates the inequality between the municipalities in distributing public resources for health (Espírito Santo, Fernando & Bezerra, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The first hypothesis (H 1 ) refers to the relationship between the supply, demand, and utilization variables. It is not possible to either confirm or refute such a hypothesis building on the determinants in the first group of models (1)(2)(3). This is particularly relevant in model 2, in which the dependent variable LOWCOMPLEX was only significantly related to NUM_ADM.…”
Section: Test Of Hypotheses and The Final Modelmentioning
confidence: 95%
“…The need to allocate the (scarce) health care resources more relationally was already pointed out by Feldstein, Piot and Sundaresan [2] some decades ago. Today, Espírito-Santo, Fernando and Bezerra [3] share a similar perspective and claim that the structural problems of the public health care system are, to some extent, related to resource allocation.…”
Section: Introductionmentioning
confidence: 97%